NEED TO CHANGE MUSIC COURSES ACCORDING TO THE CURRENT TIME: वर्तमान समयानुसार संगीत पाठ्यक्रमों में बदलाव की आवश्यकता - Moghe, Anoop (International Journal of Research -GRANTHAALAYAH, 2015)
Musical art has special significance in Indian arts. Like other arts, musical art does not imitate mental perception, rather it is an imitation of one’s own will and this act of realizing it is its shadow. This is the reason for the strong influence of music that it itself expresses the real element. Musical art does not express any particular limited joy, sorrow, suffering, fear, peace or happiness, but it gives expression to their common and universal nature. Music fills devotional feelings in our soul. भारतीय कलाओं में संगीत कला का विशेष महत्व है। संगीत कला अन्य कलाओं की तरह मानसिक बोध कराने की अनुकृति नहीं करती, बल्कि वह स्वयं की इच्छा की अनुकृति है और यह बोध कराने की क्रिया इसी की छाया है। संगीत के सशक्त प्रभाव का यही कारण है कि वह स्वयं असली तत्व की अभिव्यक्ति करता है। संगीत कला किसी विशेष सीमित आनन्द, दुःख, पीड़ा, भय, शांति या प्रसन्नता के व्यक्त नहीं करती बल्कि वह इनके सामान्य और सार्वभौमिक स्वरूप को अभिव्यक्ति देती है। संगीत हमारी आत्मा में भक्तिमय अनुभूतियां भर देता है।